OPTIMALISASI SHARI'A COMPLIANT ASSET PRICING MODEL TERHADAP RATE OF RETURN PADA JAKARTA ISLAMIC INDEX - Kharisya Ayu Effendi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2016)
This study aimed to compare the three models SCAPM, namely SCAPM without risk free, SCAPM inflation and SCAPM zakat to know which model is more optimal use. The method used is the analysis of explanatory power and linear regression. The data used is secondary data, the inflation data, zakat, sharia shares incorporated in Jakarta Islamic Index (JII) from 2011 to 2015.The results are based on the analysis of explanatory power, SCAPM inflation is more optimal than SCAPM zakat and SCAPM without risk free. The results are supported by the results of the analysis graph illustrating SCAPM inflation has a higher volatility than other SCAPM, it indicates that the more profitable inflation SCAPM models are accompanied by greater risks, in accordance with the principles of the classical high risk high return.